2001
DOI: 10.1136/bjo.85.6.678
|View full text |Cite
|
Sign up to set email alerts
|

Ocular pulse amplitude is reduced in patients with advanced retinitis pigmentosa

Abstract: Background/aims-The choroid, a low resistance vascular structure carrying 85% of the ocular blood flow, provides nourishment to and removal of potential toxic waste products from the adjacent non-vascularised outer layers of the retina, macula, and optic disc regions. Choroidal perfusion may be reduced in retinitis pigmentosa (RP) and might contribute to retinal pigment epithelium (RPE) degeneration. The aim of this study was to determine whether choroidal perfusion is reduced in RP and whether this is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
(36 reference statements)
3
34
0
3
Order By: Relevance
“…Both the mean value of the ocular pulse amplitude (2.2 ± 0.6 mmHg) and its range (1-3.4 mmHg) were in agreement with those previously reported [2,10,11].…”
Section: Discussionsupporting
confidence: 91%
“…Both the mean value of the ocular pulse amplitude (2.2 ± 0.6 mmHg) and its range (1-3.4 mmHg) were in agreement with those previously reported [2,10,11].…”
Section: Discussionsupporting
confidence: 91%
“…This increased tissue oxygen level causes a reduction in oxygen intake from retinal circulation, resulting in the lower AVS. However, choroidal blood flow was also found to be reduced in RP [42][43][44][45], which may partially counteract the effects of oxygen diffusion from the choroid.…”
Section: Discussionmentioning
confidence: 84%
“…Several previous hemodynamic studies showed a reduction in both choroidal blood flow and retinal blood flow in RP, by using color Doppler imaging and laser Doppler flowmetry (Langham and Kramer, 1990;Akyol et al, 1995;Cellini et al, 1997;Schmidt et al, 2001;Falsini et al, 2011;Grunwald et al, 1996) and in addition, other authors found a positive correlation between increased ET-1 plasma concentration and abnormalities in the microcirculation not only in the eye, but also in the whole body (Cellini et al, 2010;Konieczka et al, 2012). Notably we reported a negative association between choroidal thickness and ET-1 (r = − 0.702; p b 0.023) and hypothesize that the reduction of choroidal thickness may be determined by the vasoconstrictor effect of ET-1 which could cause choroidal vascular abnormalities and blood flow impairment with a resulting relative ischemia leading to worsening of the abiotrophic process of the macular photoreceptors.…”
Section: Discussionmentioning
confidence: 98%